2010
DOI: 10.1007/s10566-010-9121-7
|View full text |Cite
|
Sign up to set email alerts
|

Anger Mediates the Relation Between Violence Exposure and Violence Perpetration in Incarcerated Boys

Abstract: Youth who are exposed to violence are more likely to perpetrate violence. Incarcerated youth are a special population that is at a significantly greater risk for violent offending because of their relatively greater rates of violence exposure. Two important outcomes of violence exposure that may help explain its link with violence perpetration are posttraumatic stress disorder and problematic anger. The primary aim of the current study is to examine whether these important risk factors mediate the relation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 83 publications
(102 reference statements)
4
30
0
Order By: Relevance
“…Despite a plethora of research supporting a positive relationship between psychopathy and trauma history (e.g., Cima, Smeets, & Jelicic, 2008;Kimonis, Ray, Branch, & Cauffman, 2011;Weiler & Widom, 1996), its association with PTSD has been relatively understudied. Research has established a weak to moderate association between PTSD and global psychopathy (Blackburn, Logan, Donnelly, & Renwick, 2003;Blonigen, Sullivan, Hicks, & Patrick, 2012;Kubak & Salekin, 2009).…”
Section: Martin Sellbommentioning
confidence: 99%
“…Despite a plethora of research supporting a positive relationship between psychopathy and trauma history (e.g., Cima, Smeets, & Jelicic, 2008;Kimonis, Ray, Branch, & Cauffman, 2011;Weiler & Widom, 1996), its association with PTSD has been relatively understudied. Research has established a weak to moderate association between PTSD and global psychopathy (Blackburn, Logan, Donnelly, & Renwick, 2003;Blonigen, Sullivan, Hicks, & Patrick, 2012;Kubak & Salekin, 2009).…”
Section: Martin Sellbommentioning
confidence: 99%
“…Youth who are regularly exposed to community violence are more prone to become aggressive and have more cognitive deficits, limiting their ability to cope positively (Kimonis, Ray, Branch, & Cauffman, 2011). Further, researchers have found that lower socioeconomic status is associated with higher levels of CU traits in youth (Sadeh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, males tend to be more physically violent, whereas females tend to internalize problems more (Webster-Stratton, 1996). In addition to potential biological influences on CU traits, community violence affects males and females differently and possibly moderates the development of these traits (Kimonis et al, 2011). Females are more likely to develop anxiety and depression as a result of exposure to violence, while males show more distress when victimized violently compared with witnessing violence (Foster, Kuperminc, & Price, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Delinquent youths are likely to come from impoverished homes and neighborhoods (Garbarino & Plantz, 1986a, 1986b; Loeber & Stouthamer-Loeber, 1986; Rodriguez, 2011), and these communities bear the largest impact of violence exposure (Berman, Silverman, & Kurtines, 2002; Gibson, Morris & Beaver, 2009; Osofsky, 1999). Involvement in delinquent activity, moreover, is likely to expose youths to community violence and victimization (Kimonis, Ray, Branch, & Cauffman, 2011; Shaffer & Ruback, 2002). In addition, a number of prospective longitudinal studies have now found that history of trauma and violence exposure increases risk for delinquent behavior in both adolescence and adulthood (Kirk & Hardy, 2012; Maxfield & Widom, 1996; Stouthamer-Loeber, Loeber, Homish, & Wei, 2001; Thornberry, Ireland, & Smith, 2001).…”
mentioning
confidence: 99%